Badania symulacyjne algorytmu zarządzania energią w gospodarstwach domowych = Simulation research of the energy management algorithm for households - Powroźnik, Piotr; Miczulski, Wiesław (1949- ); Szulim, Robert (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents the results of the simulation tests of the flexible energy management algorithm (EZE) in a group of 1000 households (GD). GD belong to energy consumers with a great potential of saving it. The obtained results indicate that the developed EZE algorithm allows planning the behaviour of energy consumers and planning energy demand.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne